2022
DOI: 10.3390/jcs6070201
|View full text |Cite
|
Sign up to set email alerts
|

Color Stability Determination of CAD/CAM Milled and 3D Printed Acrylic Resins for Denture Bases: A Narrative Review

Abstract: The aim of this paper is to review the available literature on the different methods for color stability determination of CAD/CAM milled and 3D printed resins for denture bases. The methodology included applying a search strategy, defining inclusion and exclusion criteria and selecting studies to summarize the results. Searches of PubMed, Scopus, and Embase databases were performed independently by three reviewers to gather the literature published between 1998 and 2022. A total of 186 titles were obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…These findings coincide with Yuan et al, who found no significant color changes between CAD/CAM lithium disilicate ceramics after simulated toothbrushing [19]. Additionally, Garza et al found that no significant difference was detected for shade change over time, irrespective of the technique for the lithium disilicate fabrication [53].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These findings coincide with Yuan et al, who found no significant color changes between CAD/CAM lithium disilicate ceramics after simulated toothbrushing [19]. Additionally, Garza et al found that no significant difference was detected for shade change over time, irrespective of the technique for the lithium disilicate fabrication [53].…”
Section: Discussionsupporting
confidence: 81%
“…The current study aimed to assess the impact of toothbrushing simulation on different CAD/CAM and pressable lithium disilicate ceramics in terms of surface roughness, microhardness, and color change. Based on our findings, the Emax CAD, Emax Press, and LiSi Press groups showed a decrease in the surface roughness (Ra) after an equivalent of 1 year of toothbrushing; however, the decrease was insignificant, which may be explained by their excellent physicomechanical stability [19,30]. Additionally, no significant difference in Ra values was observed among the groups after mechanical toothbrushing (p value = 0.842).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…According to the research by Koksal and Dikbas, Brewer et al, lighter shades of teeth experience greater discolouration than darker shades [ 40 , 41 ]. Thus, the A2 shade of denture teeth was chosen for our study because it is one of the lightest shades available for the denture teeth brands [ 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The range of factors influencing possible discoloration related to individual food preferences requires the conclusion that such indicators would be difficult to define; we consider this to be one of the limitations of the study. From our searches in the available literature, similar studies on color changes differed significantly in terms of the staining period and ranged from 7 to 180 days [41][42][43][44]. In our study, we wanted to show the trend between the duration of the coloring agent and the actual color change of ZnO NP-PMMA.…”
Section: Discussionmentioning
confidence: 99%